KEPEMIMPINAN LURAH DALAM MENINGKATKAN KINERJA PEGAWAI DI KELURAHAN MENDUI KECAMATAN BUNGKU TENGAH - Fadli, Muhammad (Katalogis, 2018)
The problem of this research is How Lurah leadership in improving employee performance wards. This study analyzed descriptively qualitative. The informant in this research that a number of seven people consisting of a sub-district head, village employees and the public are drawn with purposive sampling technique. Mechanical collection and retrieval of data consists of observation, interviews, and documentation. The theory used in see headman leadership is in Timpe Chapman theory. which consists of means of communication, motivation, leadership skills, decision-making and power positive. The results showed that the Leadership Lurah Mendui in improving employee performance Sub Mendui District of Bungku Middle Morowali consisting of Giving Motivation, Ability Leads, Decision Making, and the power of positive showing leadership Lurah Mendui not maximum, but in the aspect of how to communicate to employees Lurah Mendui already perform well. That is shown by the attitude of village chief who is able to communicate in both directions with employees and give freedom of speech to employees.